Spatial characteristics of development efficiency for urban tourism in eastern China: A case study of six coastal urban agglomerations - Rui Li; Qian Guo; Dianting Wu; Hongmei Yin; Hua Zhang; Taoxing Zhu (Journal of Geographical Sciences, 2014)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Anti-depressive activities and biotransformation of timosaponin B-III and its derivatives - WeiXin Jiang; Jing Guo; Rui Xue; KaiCheng Zhu; ZhiXiong Li; MingCang Chen; ChengGang Huang (Natural Product Research, 2014)

Zircon U–Pb geochronology and geochemistry of the Maoliger quartz monzodiorites, Inner Mongolia, China: implications for Carboniferous arc magmatism and closure of the Palaeo-Asian Ocean - Li-Min Wang; Xiao-Guo Chi; Zhi Zhao; Wei Sun; Rui Zhang; Shi-Yu Pan; Jing-Yu Quan (International Geology Review, 2014)

Chemical constituents from Melastoma dodecandrum and their inhibitory activity on interleukin-8 production in HT-29 cells - Guo-Xun Yang; Rui-Ze Zhang; Bin Lou; Ke-Jun Cheng; Juan Xiong; Jin-Feng Hu (Natural Product Research, 2014)

Serum uric acid level is associated with the prevalence but not with survival of amyotrophic lateral sclerosis in a Chinese population - Zhenzhen Zheng; Xiaoyan Guo; Qianqian Wei; Wei Song; Bei Cao; Rui Huang; Ruwei Ou; Xueping Chen; Huifang Shang (Metabolic Brain Disease, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Simultaneous Determination of Calycosin-7-O-β-d-Glucoside, Ononin, Calycosin, Formononetin, Astragaloside IV, and Astragaloside II in Rat Plasma After Oral Administration of Radix Astragali Extraction for Their Pharmacokinetic Studies by Ultra-Pressure Liquid Chromatography with Tandem Mass Spectrometry - Xiao-hua Liu; Jian-bang Zhao; Long Guo; Ying-lai Yang; Fang Hu; Rui-juan Zhu; Shi-lan Feng (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Apply array induction logging to study the low-resistivity belt zone identification method - Rui Deng; Haimin Guo; Chengwen Xiao (Arabian Journal of Geosciences, 2014)

Two new species of Spadicoides and Gangliostilbe from southern China - Li-Guo Ma; Ji-Wen Xia; Ying-Rui Ma; Rafael F. Castañeda-Ruíz; Xiu-Guo Zhang (Mycological Progress, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Origin of sanukitoid and hornblendite enclaves in the Dajitu pluton from the Yinshan Block, North China Craton: product of Neoarchaean ridge subduction? - Xudong Ma; Hong-Rui Fan; M. Santosh; Xuan Liu; Jing-Hui Guo (International Geology Review, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

Effect of PGPR Serratia marcescens BC-3 and AMF Glomus intraradices on phytoremediation of petroleum contaminated soil - Rui Dong; Lijing Gu; Changhong Guo; Feifei Xun; Jiali Liu (Ecotoxicology, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zircon geochronology constraints on the age and nature of ‘Precambrian metamorphic rocks’ in the Xing’an block of Northeast China - Wei Sun; Xiao-Guo Chi; Zhi Zhao; Shi-Yu Pan; Jian-Feng Liu; Rui Zhang; Jing-Yu Quan (International Geology Review, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Irregular western margin of the Yangtze block as a cause of variation in tectonic activity along the Longmen Shan fault zone, eastern Tibet - Xiaoyu Guo; G. Randy Keller; Rui Gao; Xiao Xu; Haiyan Wang; Wenhui Li (International Geology Review, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

Interannual linkage between Arctic/North Atlantic Oscillation and tropical Indian Ocean precipitation during boreal winter - Dao-Yi Gong; Yongqi Gao; Dong Guo; Rui Mao; Jing Yang; Miao Hu; Miaoni Gao (Climate Dynamics, 2014)

Benzene containing polyhydroxyalkanoates homo- and copolymers synthesized by genome edited Pseudomonas entomophila - Rui Shen; LongWei Cai; DeChuan Meng; LinPing Wu; Kai Guo; GuoXing Dong; Lei Liu; JinChun Chen; Qiong Wu; GuoQiang Chen (Science China Life Sciences, 2014)

Identification of a novel fumarase C from Streptomyces lividans TK54 as a good candidate for l-malate production - Rui-Rui Su; Ao Wang; Song-Tao Hou; Peng Gao; Guo-Ping Zhu; Wen Wang (Molecular Biology Reports, 2014)

The role of Somatic embryogenesis receptor-like kinase 1 in controlling pollen production of the Gossypium anther - Ya-li Shi; San-dui Guo; Rui Zhang; Zhi-gang Meng; Mao-zhi Ren (Molecular Biology Reports, 2014)

Simazine degradation in bioaugmented soil: urea impact and response of ammonia-oxidizing bacteria and other soil bacterial communities - Qingwei Guo; Rui Wan; Shuguang Xie (Environmental Science and Pollution Research, 2014)

The apoptosis of peripheral blood lymphocytes promoted by hyperbaric oxygen treatment contributes to attenuate the severity of early stage acute pancreatitis in rats - Xuewei Bai; Zengfu Song; Yanmei Zhou; Shangha Pan; Feng Wang; Zuoming Guo; Maitao Jiang; Gang Wang; Rui Kong; Bei Sun (Apoptosis, 2014)